2020
DOI: 10.1111/ced.14513
|View full text |Cite
|
Sign up to set email alerts
|

Genes and phenotypes in vascular malformations

Abstract: Vascular malformations (VMs) are caused by localized defects of vascular development. Most VMs are due to sporadic, postzygotic mutations, while some are the result of autosomal dominant germline mutations. Genotype-phenotype correlation is influenced by many factors. Individual genes can induce different phenotypes (pleiotropy), and similar phenotypes can be due to different genes/mutations (redundancy). The phenotypic spectrum of somatic mutations is wide, and depends on variant allele frequency, timing duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Additionally, he had lymphangiomas, cystic lesions, lipomas, dolichocephaly, down-slanting palpebral fissures with ptosis, and a flattened nasal bridge. The patient's clinical presentation fits the clinical criteria for diagnosis of PS, as an asymmetric overgrowth syndrome that is progressive and typically noted in childhood, as presented in Figure 7 [4, 10,12,14,15]. Phenotypic presentations are induced by individual genes or different genes can produce one phenotype [16].…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, he had lymphangiomas, cystic lesions, lipomas, dolichocephaly, down-slanting palpebral fissures with ptosis, and a flattened nasal bridge. The patient's clinical presentation fits the clinical criteria for diagnosis of PS, as an asymmetric overgrowth syndrome that is progressive and typically noted in childhood, as presented in Figure 7 [4, 10,12,14,15]. Phenotypic presentations are induced by individual genes or different genes can produce one phenotype [16].…”
Section: Discussionmentioning
confidence: 98%
“…Rare diseases affect fewer than 1 in 200,000 people in the U.S. or 1 in 2,000 people in Europe 1 , 2 . Although most rare diseases are complex, disabling, and life-threatening 3 , they lack related studies and approved treatments 4 due to the limited prevalence and market 5 . Skin diseases cause significant nonfatal disability worldwide 6 , especially in resource-poor regions 7 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Methylation of specific genes is significantly correlated with the occurrence of VMs. 10 , 12 The phenotypic spectrum of somatic mutations is wide and depends on variant allele frequency, timing during embryogenesis, cell type(s) involved and type of mutation. It has been shown that in vascular endothelial cells, methyl-binding proteins bind to methylated promoters of endothelial nitric oxide synthase (eNOS) and vascular endothelial growth factor receptor 2 (VEGFR2).…”
Section: Introductionmentioning
confidence: 99%